1976
DOI: 10.1021/bi00666a016
|View full text |Cite
|
Sign up to set email alerts
|

Chromatographic and functional comparison of human placenta and HeLa cell tyrosine transfer ribonucleic acids

Abstract: Chromatographic and functional properties of tyrosine isoaccepting transfer ribonucleic acids (tRNAs) from placenta and HeLa cells were analyzed and compared. RPC-5 chromatography separated four major isoacceptors from each source, with those from HeLa cells eluting generally later than those from placenta. There was some overlap: HeLa tRNA1Tyr eluted in a position between placenta tRNA3Tyr and tRNA4Tyr; and HeLa tRNA2Tyr and placenta tRNA4Tyr eluted in similar positions with the HeLa isoacceptor eluting sligh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

1979
1979
1992
1992

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…The codon.-depen.dent ribosome binding ability of the late-eluting tRNAAsp and an earlier eluting tRNAAsp were compared and found to be approximately the same. If the late-eluting peak in these studieA [21,22] is identical to our wobble-guanosine containing late-eluting peak, it would therefore seem that the function. of these tRNAs in protein synthesis associated reaction.s is independent of the Q modification in.…”
Section: Resultsmentioning
confidence: 63%
See 3 more Smart Citations
“…The codon.-depen.dent ribosome binding ability of the late-eluting tRNAAsp and an earlier eluting tRNAAsp were compared and found to be approximately the same. If the late-eluting peak in these studieA [21,22] is identical to our wobble-guanosine containing late-eluting peak, it would therefore seem that the function. of these tRNAs in protein synthesis associated reaction.s is independent of the Q modification in.…”
Section: Resultsmentioning
confidence: 63%
“…A recent report by Olsen. and Penhoet [22] describing comparative studies of tRNATyr from human. placenta an.d HeLa cells indicates that no significant differences exist in.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…tRNAtYr and tRNAty3r, which were not well resolved by the chromatography conditions we employed, decreased gradually during the course of differentiation relative to the other species. Comparative studies of tRNAtyr from normal human placenta and HeLa cells indicated that no significant differences existed in the rate or site of incorporation of tyrosine into tryptic peptides of a-globin, even though there was again a dramatic difference in the RPC-5 chromatographic profiles between the tRNAs of these two tissues (17).…”
Section: Tymentioning
confidence: 94%